Rough Cut Capacity Planning dengan Menggunakan Matriks Skill dalam Pemenuhan Order di PT X Manufaktur Furnitur - Arifin, Muhamad; Tjandra, Sugih Sudharma (Universitas Katolik Parahyangan, 2024)
The COVID-19 pandemic has had a significant impact on a variety of sectors, including the furniture manufacturing industry. The industry is undergoing drastic demand changes, complicating adjustment efforts during the pandemic. Additional human resources (HRM) is becoming a more complex challenge due to strict health protocols and the necessary vaccination efforts. In this context, increased availability of capacity has become critical, but an appropriate approach has not been revealed in the literature. As for the in-depth literature study, it covers various methods of increasing production capacity, such as adding human resources, machines, shift work systems, overtime, and subcontractors. The research focuses on a new way to multi-skill by using the skill matrix as an innovative method to increase the availability of capacity at PT X, a furniture manufacturing company. Using Rough Cut Capacity Planning (RCCP), the study describes current production capacity, analyzes the impact of post-COVID demand shifts, and evaluates the effectiveness of multi-skill application with a skill matrix in improving production flexibility and responsiveness. The research findings provide valuable insights for furniture companies and related sectors in dealing with post-COVID dynamics, as well as providing the basis for developing more adaptive and sustainable capacity planning strategies.